(3aJGhi bGVj NGfs - (3bGVj NGf, MSf Hf efUhQ Hf CHj GdbGSe, J (B592 (3g`s ((3eMeO Hf GdMGL bQWs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi QShdg eMeO hBdg CLejYf bGd GdbGVj GdEeGe GdMSf Hf efUhQ Hf eMehO GdChRLfOj jbhd GdYHO GdVYja GdChRLfOj PcQJ aj gPG GdcJGH ef GdeSGFd GdJj jcKQ hbhYgG hJeS GdMGLI EdjgG s
(3BNQgG (B:s
(3ajfaP gPG GdbVGA adG jfaP CHWGd GdKGfj MLQ GdChd hYf CHj HcQ GdHdNj Cfg deG SFd Yf eMLhQ Ydjg hba VjYI bGd hbag HGWd EdG Cf jCPf dg bGVj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 224s
(3eYLe GdeDdajf (B1 / 594s
(3cTa GdXfhf (B2 / 1227s
(3TPQGJ GdPgH (B4 / 308s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs